(untitled) (Journal of Bangladesh Institute of Planners, 2021)
In general, this paper focuses on low-income housing, city planning and the state’s intention in building a new housing project called Bhashantek Rehabilitation Project (BRP) in Dhaka, Bangladesh. In particular, it explores how BRP became a "failure" project dominated by different types of elites. Access to housing here in BRP is negotiated in the continuously changing arrangements of a complex between formal and informal rules and regulations. By focusing on this specific issue, this paper argues that the project was based on an exclusionary construction in the interactions within the project itself. It also examines how the dynamics of intermediaries further complicated the project. In addition, while acknowledging the power of the state’s patronage for a particular class, such as the developer and the bureaucratic apparatus, this paper brings together many other issues on prevalent discourse on scientific city planning. JBIP, Vol. 14, 2021, pp. 1-25